Kościół katolicki w kazaniach Jakuba Wujka. Uwagi wstępne - Migdał, Jolanta (Slavia Occidentalis, 2023)
This article is a preliminary reconnaissance of Jakub Wujek’s presentation in his Lesser Postylla sermons of the Catholic Church and the truths of faith he preached. This reconnaissance confirms that the circumstances of the creation of Wujek’s Lesser Postylla, its genesis, strongly influenced the content of the work. For the universal, Catholic Church was almost always presented by the Jesuit preacher in confrontation with the image of the criticised dissenters. Notably, the picture of the true Church as presented by Wujek in his sermons is fully in line with the doctrine of this religion. Undoubtedly, the picture of the Church painted almost five centuries ago is still valid, as confirmed by confronting Wujek’s remarks with the contemporary version of the official interpretation of the Catholic Church’s doctrine of faith and morals, the Catechism of the Catholic Church, compiled in the second half of the 20th century after the Second Vatican Council.